Fostering Students' Mathematical Communication Skills in Mathematics Learning - Tia Fitri Nuraini; Nindy Cahyani Haditia; Arif Rahman Hakim; Nur Indah Sari (ISEJ : Indonesian Science Education Journal, 2022)
This article is the result of a literature review (theory of findings) regarding mathematical communication skills in learning mathematics. This article was written with the aim of providing a thorough understanding of mathematical communication skills as well as describing various alternative ways of building students' mathematical communication skills in learning mathematics. The results obtained from writing this article are in the form of a description of the definition of mathematical communication skills, descriptions of indicators of mathematical communication skills, and descriptions of efforts to develop mathematical communication skills in students. With these results, obtained a way how teachers can build and develop mathematical communication skills in students in each process of learning mathematics activities. Through this article, it can be concluded that teachers in learning mathematics must be able to carry out various learning activities that can clearly develop students in terms of mathematical communication skills.